2016
DOI: 10.1097/ico.0000000000000777
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intraductal Meibomian Gland Probing on Tear Function in Patients With Obstructive Meibomian Gland Dysfunction

Abstract: Intraductal meibomian gland probing demonstrated significant efficacy in symptom relief and tear film stabilization. Probing helped release accumulated meibum and could help increase the accessibility of diseased meibomian glands to topical corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 26 publications
3
61
0
Order By: Relevance
“…Although the safety and effectiveness of IPL and MGP have been proved by previous studies 8,9,[11][12][13] , the deficiency of IPL and MGP could also be observed in our day-to-day clinical observation. The effect of IPL to open stubborn intraductal congestion or intraductal scar is comparatively limited.…”
Section: Introductionsupporting
confidence: 47%
See 2 more Smart Citations
“…Although the safety and effectiveness of IPL and MGP have been proved by previous studies 8,9,[11][12][13] , the deficiency of IPL and MGP could also be observed in our day-to-day clinical observation. The effect of IPL to open stubborn intraductal congestion or intraductal scar is comparatively limited.…”
Section: Introductionsupporting
confidence: 47%
“…Meibomian gland probing opened the obstructed orifices and ducts mechanically. With the pop up of constrained meibum, keratinized epithelium and debris, vicious cycle of o-MGD progression was broken and the majority of patients received immediate relief of symptoms 11,16 . However, the quantity of meibum in ocular surface is not a decisive factor in retarding the evaporation of aqueous and stabilizing the tear film.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 A randomised, controlled study of 25 patients with obstructive MGD showed that both signs and symptoms were improved one month after probing. 57 Other studies have demonstrated the safety and efficacy of probing for patients with obstructive MGD. [58][59][60] Moreover, probing was associated with an increase in meibomian gland area 61 as determined by non-invasive meibography.…”
Section: Intraductal Probingmentioning
confidence: 99%
“…Intraductal probing is a highly invasive procedure, which has been reported to offer functional improvement in the most severe cases of obstructive MGD that are unresponsive to other forms of treatment . Further research is required to confirm the absence of structural or fibrotic damage, to the fragile gland structures, in the longer term.…”
Section: Optimising Tear Film and Ocular Surface Health For Contact Lmentioning
confidence: 99%